The biobehavioural pain and movement questionnaire (BioPMovQ): development and psychometric validation of a new questionnaire - La Touche, Roy; Paris-Alemany, Alba; Pardo-Montero, Joaquín; Miñambres-Martín, Diego; Mercado-Romero, Francisco; de la Rosa-Díaz, Irene; Sorrel, Miguel A.; Grande-Alonso, Mónica (Frontiers in Medicine, 2024)
Objective: The purpose of this research was to design and psychometrically validate a new instrument (the Biobehavioural Pain and Movement Questionnaire/BioPMovQ), which assesses the relationship between pain and various factors related to motor behaviour from a biobehavioural perspective.A mixed-method design combining a qualitative study with an observational and crosssectional study was employed to develop (content validity) and psychometrically validate (construct validity, reliability and concurrent/discriminant validity) a new instrument. A total of 200 patients with chronic musculoskeletal pain were recruited.Results: According to the exploratory factor analysis, the final version of the BioPMovQ consists of 16 items distributed across 4 subscales (1, disability; 2, self-efficacy for physical activity; 3, movement avoidance behaviours; and 4, self-perceived functional ability;), all with an eigen value greater than 1, explaining 55.79% of the variance. The BioPMovQ showed high internal consistency (Cronbach's α=0.82; McDonald's ω=0.83). The intraclass correlation coefficient was 0.86 (95% confidence interval 0.76 to 0.91), which was considered to demonstrate excellent test-retest reliability. The standard error of measurement and minimal detectable change were 3.43 and 8.04 points, respectively. No floor or ceiling effects were identified. There was a positive, significant and moderate magnitude correlation with the Graded Chronic Pain Scale (r=0.54), kinesiophobia (r=0.60), pain catastrophising (r=0.44) and chronic pain self-efficacy (r=-0.31).The BioPMovQ showed good psychometric properties. Based on the findings of this study, the BioPMovQ can be used in research and clinical practice to assess patients with chronic musculoskeletal pain. 1 GCPS **0.52 **0.55 **0.27 **0.39 **0.38 GCPS Disability **0.51 **0.54 **0.28 **0.34 **0.35 GCPS Pain Intensity **0.44 **0.40 *0.17 **0.38 **0.33 NPRS **0.31 *0.17 *0.15 **0.28 **0.26 TSK-11 **0.60 **0.45 **0.22 **0.53 **0.54 TSK Harm **0.51 **0.25 **0.51 **0.32 **0.38 TSK Activity Avoidance **0.32 **0.35 *0.14 **0.34 **0.37 PCS **0.44 **0.43 *0.18 **0.32 **0.38 PCS Rumination **0.39 **0.37 **0.22 **0.28 **0.33 PCS Magnification **0.32 **0.31 **0.16 **0.24 **0.26 PCS Helplessness **0.42 **0.44 0.13 **0.31 **0.39 CPSS **-0.31 **-0.32 **-0.44 **-0.22 **-0.21 PSE **-0.26 **-0.27 **-0.37 **-0.19 **-0.19 SSE **-0.26 **-0.29 **-0.40 **-0.21 **-0.18 FSE **-0.27 **-0.25 **-0.34 *-0.16 **-0.18